Factors affecting perioperative complications in upper airway surgery for obstructive sleep apnea - Asha'ari, Zamzil Amin; K.S, Sathananthar (2015)
Objective: To determine factors that affect the incidence of perioperative complications in adult patients undergoing upper airway surgery for obstructive sleep apnea (OSA). Materials & Methods: The records of 128 adult patients, diagnosed with obstructive sleep apnea (apnea-hypopnea index (AHI) >5), who underwent upper airway surgery at a single tertiary referral hospital from 2007 to 2014 were reviewed. Pulmonary, surgical, and cardiovascular complications within the first 30 postoperative days were analysed according to types of upper airway surgery. Upper airway surgery types were single surgery or combinations of surgery to the tonsils, pharyngeal adenoids, soft palate, tongue base and nose. Logistic regression was used to assess the multivariable association of age, sex, BMI, OSA severity, medical comorbidity, and types of upper airway surgery with postoperative complications. Results: At least one perioperative complications occurred in 48 of 128 patients (37.5%). In a multivariable model, the overall complication rate was increased with the age, obesity, smoking and underlying comorbid medical problems. Complication rates were not associated with OSA severity, types of procedures performed and whether the surgery was a single or combination surgery. Conclusion: In OSA patients undergoing upper airway surgery, the severity of OSA as assessed by the AHI, and the sites and numbers of concurrent surgery performed were not associated with the rate of perioperative complications.